THE SPECIAL GUIDE TEACHER CLASS MANAGEMENT ON CREATING INCLUSIVE STUDENT LEARNING MOTIVATION IN URBAN AREA - Gunawan, Agus; Habibi, Habibi; Maulahamdi, Hudisa (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
This research objective was to analyse the influence of special supervising teachers' classroom management on creating inclusive student learning motivation in urban areas. This research used quantitative methods with a case study approach. A sampling of special supervisor teachers for inclusive classes in Serang City or urban areas. Data analysis used hypothesis testing with SPSS software version 23.00 with correlation between variables. The research results showed a positive influence between the class management of the class supervisor on creating inclusive student learning motivation with an influence contribution of 70.9%. The results showed a significant influence between accompanying teachers' classroom management and student learning motivation in inclusive elementary schools throughout urban areas. The research implied that the better the accompanying teacher's classroom management, the higher contribution to inclusive student learning motivation and vice versa; the less good the accompanying teacher's classroom management, the lower the creation of inclusive student learning motivation.